Analysis of Vehicle Volume Projection and Manager Revenue from the Existence of Balikpapan Samarinda Toll Road Infrastructure Development - Rachmadi, Revy Fadly Robby; Hilmawan, Rian (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to determine the volume of vehicles (based on their groups) and the receipt of managers from the existence of the Balikpapan Samarinda Toll Road infrastructure development, then project and analyze the volume of vehicles and the receipt of managers (according to their groups) within the next one year that cross the Balikpapan Samarinda Toll Road. This study uses secondary data obtained from the Balikpapan Samarinda Toll Road manager, namely PT. Jasa Marga Balikpapan Samarinda. The method used to project is Forecasting with Autoregressive (AR) and Moving Average (MA) regression models and processed using Eviews 12 software. The results of this study show that the volume of vehicles and the receipt of managers (based on their groups) that cross the Balikpapan Samarinda Toll Road after its operation shows fluctuating results with group I dominating with the highest volume of vehicles among groups II-V. Then, the results of the projection of vehicle volume (based on the group) in the next one year show an increasing trend with an average increase in percentage of each group, namely Group I of 50% or 42,078 units, Group II of 64% or 5,465 units, Group III of 51% or 1,478 units, Group IV of 81% or 229 units, Group V of 78% or 763 units. Meanwhile, the projected results of managerial revenues also show an increasing trend from January to December 2023 with an average increase in percentage of 39% and an amount in rupiah of IDR 3,096,815,146.00. For a complete explanation, you can read more